Embryonic neuronal markers in tuberous sclerosis: Single-cell molecular pathology - Crino, Peter B. (The National Academy of Sciences of the USA, 1996)
One hallmark of tuberous sclerosis (TSC) is the presence of highly epileptogenic dysplastic cerebral cortex (tubers) composed of abnormally shaped neurons and giant cells. Mutation of the TSC gene (TSC2) may disrupt differentiation and maturation of neuronal precursors, since the TSC2 gene product tuberin is believed to regulate cellular proliferation. To test the hypothesis that cells in tubers may retain the molecular phenotype of embryonic or immature neurons, tubers from five TSC patients were probed with antibodies to proteins expressed in neuronal precursors (nestin, Ki-67, and proliferating cell nuclear antigen). Many dysmorphic neurons and giant cells in tubers were stained by these antibodies, while neurons in adjacent normal and control cortex were not labeled. To further characterize the molecular phenotype of cells in tubers, we developed a methodology in which poly(A)(+) mRNA was amplified from immunohistochemically labeled single cells in paraffin-embedded brain specimens. This approach enabled us to detect mRNAs encoding nestin, and other cytoskeletal elements, cell cycle markers, and synthetic enzymes present in individual nestin-stained cells by means of reverse Northern blotting. We conclude that the presence of immature phenotypic markers (mRNAs and proteins) within tubers suggests disruption of cell cycle regulation and neuronal maturation in TSC during cortical development. Characterization of multiple mRNAs within fixed, immunohistochemically labeled cells provides a powerful tool for studying gene expression and the molecular pathophysiology of many neurologic diseases.